2023
DOI: 10.3390/foods12050991
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Oat (Avena sativa L.) and Pea (Pisum sativum L.) Saponins in Plant-Based Food Products by Hydrophilic Interaction Liquid Chromatography Coupled with Mass Spectrometry

Abstract: This work presents the sample extraction methods for solid and liquid sample matrices for simultaneous quantification of oat (Avena sativa L.) and pea (Pisum sativum L.) saponins: avenacoside A, avenacoside B, 26-desglucoavenacoside A, and saponin B and 2,3-dihydro-2,5-dihydroxy-6-methyl-4H-pyran-4-one (DDMP) saponin, respectively. The targeted saponins were identified and quantified using a hydrophilic interaction liquid chromatography with mass spectrometric detection (HILIC-MS) method. The simple and high-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Soyasaponins were extracted according to the previously published method developed for pea and oat saponins [30] with some modifications. Briefly, the thawed homogeneous liquid sample was weighed (0.35-0.40 g) into a 5 mL volumetric flask (n = 3).…”
Section: Extraction Methods For Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Soyasaponins were extracted according to the previously published method developed for pea and oat saponins [30] with some modifications. Briefly, the thawed homogeneous liquid sample was weighed (0.35-0.40 g) into a 5 mL volumetric flask (n = 3).…”
Section: Extraction Methods For Samplesmentioning
confidence: 99%
“…Analysis was performed as described previously [30] with adaptations to the analysis of soyasaponins. Briefly, a Waters UPLC ® system (Waters Corporation, Milford, MA, USA) attached to a Waters Quattro Premier XE Mass Spectrometer equipped with ZSpray™ Source was used to analyse the samples.…”
Section: Liquid Chromatography Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Aglycone form Yoshiki et al, 1998;Hu et al, 2002;Fang et al, 2004;Rickert et al, 2004;Serventi et al, 2013Price et al, 1988Ruiz et al, 1996;Kerem et al, 2005;Serventi et al, 2013Daveby et al, 1997Heng, Vincken, Hoppe, van Koningsveld, Legger, et al, 2006;Heng, Vincken, Hoppe, van Koningsveld, Decroos, et al, 2006;Reim & Rohn, 2015Ruiz et al, 1996Pecio et al, 2012Günther-Jordanland et al, 2016;Bljahhina et al, 2023 *Found in hypocotyl of soybean seed and not in protein ingredient. Daveby et al (1997) observed only saponin Bb to be present in peas but acknowledge that the preparation of the extracts may have contributed to the decomposition of the ßg saponin.…”
Section: Non-volatile Organic Compoundsmentioning
confidence: 99%
“…The consumption of saponins often results in the breakdown of red blood cells, limiting protein digestion and vitamin and mineral absorption, leading to hypoglycemia [75]. Saponins can also attach to intestinal cells and interfere with the nutrient absorption of the intestinal membrane, causing diarrhea and vomiting, and in severe cases, leaky gut [76].…”
Section: Saponinmentioning
confidence: 99%